Particulate Matter Pollution in Urban Cities of India During Unusually Restricted Anthropogenic Activities - Yadav, Ravi; Vyas, Pushpendra; Kumar, Praveen; Sahu, Lokesh Kumar; Pandya, Umangkumar; Tripathi, Nidhi; Gupta, Mansi; Singh, Vikram; Dave, Pragnesh N.; Rathore, Devendra Singh; Beig, Gufran; Jaaffrey, S. N. A. (Frontiers in Sustainable Cities, 2022)
The outbreak of COVID-19 is a global public health challenge and affected many countries, including India. The nationwide Lockdown was imposed in India from 25 March to 31 May 2020 to prevent the growth and transmission of COVID-19. The study intends to assess the impact of restrictions during the various phases of the COVID-19 Lockdown (LDN) period on daily mean concentrations of PM2.5 and PM10 in six populated cities of Jaipur, Jodhpur, Kota, Udaipur, Ajmer, and Alwar in the state of Rajasthan. The investigation has been done for the different periods, including pre-lockdown-PRELD (01 January-04 March 2020), partial lockdown-PLDN (05-24 March 2020), COVID-19 lockdown-LDN (25 March-31 May 2020), and unlocking-ULC (1 June-31 August 2020) phases. We have also compared the mean concentrations of PM2.5 and PM10 with the same period of the year 2019. A significant improvement in the air quality during the COVID-19 LDN period was noticed in all cities compared to the PRELD 2020 and the same period of the year 2019. However, the levels of PM2.5 and PM10 were seen to rise during the second, third, and fourth LDN phases compared to the first LDN, indicating subsequent lockdowns started with some relaxations and dusty conditions. On the other hand, wind-blown dust is another vital source of PM10, resulting in high concentrations in the summer months(April-May). The significant reductions in PM2.5 ( 25-50%) and PM10 (20-37%) in all six cities during the LDN period compared with PRELD were estimated. However, with significant variations from city to city, the lowest reductions in PM2.5 ( 25%) and PM10 ( 20%) were measured in Jodhpur and Ajmer, respectively. It is noticed that the episodes of rainfall and transport of oceanic air masses resulted in a reduction of particles during the ULC period compared to the LDN period. The air quality index was more or less in the "Good to satisfactory" category during the first 3 LDN periods, whereas moderate for Jodhpur, Jaipur, and Ajmer during the last LDN period. The study will be helpful to determine the mitigation policies to minimize air pollution, especially in developing regions.